Physical Risks in terms of Occupational Health and Safety in Underground Coal Mines - Ali Ekrem Aritan; Cem Şensöğüt (International Journal of Economic and Environment Geology, 2022)
Mining is one of the oldest professions in history. Along with the development of human life, mines also give direction to civilization and the economy. Mining activities carry various risks in terms of occupational health and safety (OHS). These risks can be examined under the main headings of work accidents and occupational diseases. As a result, thousands of workers face illness and death every year. Additionally, economic losses occur as a result of production interruption and stopping. Despite all the efforts to reduce mining accidents, statistics show that underground mining is one of the riskiest among all working industries. It is seen that the physical risk factors encountered in the mining sector line are remarkable in terms of risk factors. Physical risk factors that may be encountered in mines are dust, noise, vibration, lighting problems, and thermal conditions. It is essential to take measures to assess these risks and ensure the comfort of employees where each physical risk factor needs to be examined separately. In this study, physical risks being frequently encountered in underground coal mines are taken into account with recommendations for the risks.